Factors associated with anemia among children in South and Southeast Asia: a multilevel analysis - Dev Ram Sunuwar; Devendra Raj Singh; Pranil Man Singh Pradhan; Vintuna Shrestha; Pushpa Rai; Sunil Kumar Shah; Bipin Adhikari (BMC, 2023)
Abstract Background South and Southeast Asian countries (SSEA) account for the highest burden of anemia globally, nonetheless, progress towards the decline of anemia has almost been stalled. This study aimed to explore the individual and community- level factors associated with childhood anemia across the six selected SSEA countries. Methods Demographic and Health Surveys of SSEA countries (Bangladesh, Cambodia, India, Maldives, Myanmar, and Nepal) conducted between 2011 and 2016 were analyzed. A total of 167,017 children aged 6-59 months were included in the analysis. Multivariable multilevel logistic regression analysis was used to identify independent predictors of anemia. Results The combined prevalence of childhood anemia across six SSEA countries was 57.3% (95% CI: 56.9-57.7%). At the individual level, childhood anemia was significantly higher among (1) mothers with anemia compared to non-anemic mothers (Bangladesh: aOR = 1.66, Cambodia: aOR = 1.56, India: aOR = 1.62, Maldives: aOR = 1.44, Myanmar: aOR = 1.59, and Nepal: aOR = 1.71); (2) children with a history of fever in the last two weeks compared to those without a history of fever (Cambodia: aOR = 1.29, India: aOR = 1.03, Myanmar: aOR = 1.08), and; (3) stunted children compared to those who were not (Bangladesh: aOR = 1.33, Cambodia: aOR = 1.42, India: aOR = 1.29, and Nepal: aOR = 1.27). In terms of community-level factors, children with mothers in communities with a high percentage of community maternal anemia had higher odds of childhood anemia in all countries (Bangladesh: aOR = 1.21, Cambodia: aOR = 1.31, India: aOR = 1.72, Maldives: aOR = 1.35, Myanmar: aOR = 1.33, and Nepal: aOR = 1.72). Conclusion Children with anemic mothers and stunted growth were found vulnerable to developing childhood anemia. Individual and community-level factors identified in this study can be considered to develop effective anemia control and prevention strategies.